Phytochemical investigation and evaluation of antioxidant and antidiabetic activities in aqueous extracts of Cedrus atlantica - Idrissi Amine Mounadi; Mahraz Mohamed Adil; Drioua Soufiane; Assouguem Amine; Ali Essam A.; Ibrahim Mohamed A.; Mehta Chandra Mohan; Lahlali Rachid; Tlemcani Sara; Moussaoui Fatima; En-nabety Ghizlan; Eloutassi Noureddine; et al. (Open Chemistry)
Diabetes mellitus is a global health problem requiring innovative approaches for effective management. Natural compounds derived from medicinal plants offer promising avenues due to their diverse biological activities. The aim of this study was to assess the inhibitory effects of Cedrus atlantica extracts on the enzymes α-amylase and α-glucosidase, which play a crucial role in the regulation of postprandial glucose levels, as well as to investigate their phytochemical composition and antioxidant capabilities. Aqueous extract of bark (EA), aqueous extract of cones (CA), and aqueous extract of leaves (FA) of C. atlántica were prepared and evaluated for enzyme inhibition using acarbose as a standard. The CA extract showed potent α-amylase inhibition (IC50 307 ± 0.02 μg/mL) and remarkable α-glucosidase inhibition (IC50 70 ± 0.04 μg/mL), outperforming the FA and EA extracts. Quantitative analysis revealed that EA and CA extracts had higher total phenolic content, flavonoid content, and tannin content than FA extract. Antioxidant assessments highlighted the outstanding performance of CA extract, with a low IC50 ABTS (30.65 ± 0.1 μg/mL) and an impressive EC50 FRAP (59.43 ± 1.19 μg/mL), outperforming FA extract. The results demonstrate the remarkable antidiabetic potential of C. atlantica extracts, particularly the CA extract, by inhibiting key enzymes involved in carbohydrate digestion. These extracts possess various phytochemical compounds with significant antioxidant capacities, suggesting that they are suitable for pharmaceutical, nutraceutical, and cosmetic applications. Further research to isolate and identify the bioactive compounds in CA extract could lead to new therapeutic strategies for managing diabetes and oxidative stress-related conditions.